PENGELOLAAN ASET DESA YANG EFEKTIF DAN EFISIEN MELALUI PENERAPAN SISTEM MANAJEMEN ASET DESA, DESA KAMANGI BINA LAHAN DISTRIK TANAH MIRING - Awotkay, Apolinaris; Kastanya, Mensy Otelyo; Tandora, Laurensius Ricky (Musamus University, 2023)
This community service activity takes the form of outreach to village heads, village officials, and the community regarding effective and efficient management of village assets through the implementation of a village asset management system. The general goal to be achieved in is to provide insight or knowledge regarding the effective and efficient management of Village Assets through the implementation of asset management as well as to improve structured, transparent and accountable asset management and to provide education on how developing village assets. The method used in this service activity is socialization including the development of lecture material, case studies, discussions and questions and answers. The material provided during the socialization was village asset management material by implementing an effective and efficient village asset management system. The socialization resulted in an increased understanding of effective and efficient management of village assets through the implementation of a village asset management system.